2021
DOI: 10.1126/sciadv.abe8671
|View full text |Cite
|
Sign up to set email alerts
|

Anti-EGFR VHH-armed death receptor ligand–engineered allogeneic stem cells have therapeutic efficacy in diverse brain metastatic breast cancers

Abstract: Basal-like breast cancer (BLBC) shows brain metastatic (BM) capability and overexpresses EGFR and death-receptors 4/5 (DR4/5); however, the anatomical location of BM prohibits efficient drug-delivery to these targetable markers. In this study, we developed BLBC-BM mouse models featuring different patterns of BMs and explored the versatility of estem cell (SC)–mediated bi-functional EGFR and DR4/5-targeted treatment in these models. Most BLBC lines demonstrated a high sensitivity to EGFR and DR4/5 bi-targeting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…However, clinical benefits, such as longer survival, were limited to patients with LM derived from breast cancer. We previously established LM mouse models using patient-derived breast cancer cells and showed that SC delivery of targeted therapeutics is a promising approach for LM ( 57 ). In this study, we engineered SC N1KO secreting GM-CSF and scFvPD-1 to treat immunosuppressive PTEN-deficient melanoma LM mouse models and investigated the immune profile and therapeutic efficacy after IT injection of TSC-G/P.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical benefits, such as longer survival, were limited to patients with LM derived from breast cancer. We previously established LM mouse models using patient-derived breast cancer cells and showed that SC delivery of targeted therapeutics is a promising approach for LM ( 57 ). In this study, we engineered SC N1KO secreting GM-CSF and scFvPD-1 to treat immunosuppressive PTEN-deficient melanoma LM mouse models and investigated the immune profile and therapeutic efficacy after IT injection of TSC-G/P.…”
Section: Discussionmentioning
confidence: 99%
“…Human SCs (UC Davis) were grown in DMEM supplemented with 10% (vol/vol) FBS, 1% (vol/vol) L-glutamine, 1% (vol/vol) P/S, and recombinant human fibroblast growth factor hFGF (40 ng/mL; R&D Systems). Both RAW264.7 (ATCC) and CT2A (ATCC) murine cell lines and the human cell lines BMET0.2 [ 44 ], LN229-IL13Ra2, LN229-EGFRVIII and MDA-BM-231 (J. Massagué, Memorial Sloan Kettering Cancer Center), were cultured in DMEM supplemented with 10% (vol/vol) FBS and 1% (vol/vol) P/S. The NK92 (ATCC) cell line was cultured in alpha minimum essential medium (α-MEM), L-glutamine 1% (vol/vol), 1.5 g/L sodium bicarbonate, 0.2 mM inositol, 0.1 mM 2-mecroptoethanol, 0.1 mM folic acid, 12.5% horse serum, 12.5% (vol/vol) FBS, 1% (vol/vol) P/S and 100 U/mL hIL-2.…”
Section: Methodsmentioning
confidence: 99%
“…The combination of nanobodies with another ligand or molecule has been used in many studies, and its benefits in the treatment of various diseases have been investigated. In a landmark study by Kitamura et al [ 23 ], a combination of anti-EGFR nanobody and TNF-related apoptosis-inducing ligand (TRAIL) that binds to the DR4/5 receptor was used to treat breast cancer. In this project, the effect of each of these factors on breast cancer cells was investigated, and it was shown that anti-EGFR nanobody and death receptor ligand (DRL) alone have little apoptotic effect on cancer cells, but when these two molecules are joined together, they can effectively induce apoptosis in TNBC cells.…”
Section: Introductionmentioning
confidence: 99%
“…These mesenchymal stem cells were used in mouse models of residual tumor after macro-metastasis resection, perivascular niche micro-metastasis, and leptomeningeal metastasis. The results showed that the secretion of the designed molecule by mesenchymal stem cells reduced the tumor volume and increased the survival of mice [ 23 ].…”
Section: Introductionmentioning
confidence: 99%